Penelitian pembuatan komponen PVC untuk bahan bangunan (enternit PVC) dengan variasi filler serat batang pisang dan CaCO3 - Siti Rochani (Majalah Kulit, Karet, dan Plastik, 1987)
This research is an experiment which use plastic material for making enternit. The plastic material is made of PVC resin 100 phr. by adding ingredients DOP 35 phr., EPO 5 phr., BaCdZn 3.5 phr., Stearic Acid 0.75 phr., CaCO3 varied 50-90 phr., and fibre of banana stem 20-40 phr. The experiment result proved that the PVC plastic material can made enternit sheet. The optimum value of physical properties is achiven by the PVC compound which using CaCO3 90 phr. and banana stem 40 phr.